Dairy propionibacteria: less conventional probiotics to improve the human and animal healt - Zarate, Gabriela del Valle (2012)
Probiotics are live microorganisms that confer health benefits to the host when administered in adequate amounts. In the last decades there has been a great interest from food and pharmaceutical industries to develop products containing probiotics due to the great demands of healthy foods and alternatives to conventional chemotherapy. Although the great bulk of evidence concerns lactobacilli and bifidobacteria, since they are members of the resident microbiota in the gastrointestinal tract, other less conventional genera like Saccharomyces, Streptococcus, Enterococcus, Pediococcus, Leuconostoc and Propionibacterium have also been considered. The genus Propionibacterium has been historically divided, based on habitat of origin, into “dairy” and “cutaneous” microorganisms which mainly inhabit dairy/silage environments and the skin/intestine of human and animals, respectively. Dairy propionibacteria are generally recognized as safe microorganisms whereas members of the cutaneous group have shown to be opportunistic pathogens in compromised hosts. In consequence, the economic relevance of propionibacteria derives mainly from the industrial application of dairy species as cheese starters and as biological producers of propionic acid and other metabolites like exopolysaccharides and bacteriocins to be used as thickeners and foods preservers, respectively. However, the ability of dairy propionibacteria to improve the health of humans and animals by being used as dietary microbial adjuncts has been extensively investigated. In this sense, our research group has been studying for the last two decades the probiotic properties of dairy propionibacteria isolated from different ecological niches. In the present article the current evidences supporting the potential of dairy propionibacteria to be used as probiotics are reviewed focusing in a less studied mechanism such as the protection of the intestinal mucosa by the binding of dietary toxic compounds. Nowadays there are clear evidences that propionibacteria used alone or combined with other microorganisms can exert beneficial effects in the host. Dairy propionibacteria have proven to posses many promising properties such as the production of nutraceuticals like vitamin B2, B12, K and conjugated linoleic acid, and their health promoting effects could be attributed to one or more of the following modes of action: i) influence on gut microbial composition and exclusion of pathogens; ii) modulation of the metabolic activities of the microbiota and host, and iii) immunomodulation. The most documented probiotic effects for propionibacteria within these categories include: bifidogenic effect in the human gut, improvement of nutrients utilization, hypocholesterolemic effect and anticarcinogenic potential immune system stimulation. Different studies have also described the ability of dairy propionibacteria to bind and remove toxic compounds from different environments such as the gut and food. Some of them have focused in the removal of mycotoxins, like Aflatoxin B and Fusarium sp. toxins by in vitro, ex vivo and in vivo assays whereas others have reported the binding of cyanotoxins and some heavy metals like cadmium and lead. It has been proposed that probiotic microorganisms may reduce by binding, the availability of free toxic compounds within the intestinal tract which reduces in turn, their negative effects. In this respect, in recent years we have been investigating the potential of dairy propionibacteria to protect the intestinal mucosa from the toxic and antinutritional effects of some common dietary substances like the plant lectins from the Leguminosae family. By in vitro and in vivo studies we have determined that certain strains are able to bind and remove different dietary lectins from media, preventing their cytotoxic effects on intestinal epithelial cells. Daily ingestion of P. acidipropionici CRL 1198, a dairy strain studied in our laboratory, at the same time than concanavalin A prevented the deleterious effects caused by this lectin on some morphological and physiological parameters related to intestinal functionality in mice. Propionibacteria reduced the incidence of colonic lesions, the enlargement of organs, the disruption of brush border membranes and the decrease of their disaccharidase activities. Since consumption of suitable propionibacteria may be an effective tool to avoid lectin-epithelia interactions, further investigations on their potential as probiotic detoxifying agents are actually ongoing With regard to animals’ health it has been reported that dairy propionibacteria directly fed to farm animals increased weight gain, food efficiency and health of many animals like chickens, laying hens, piglets and cows. With a wider insight, propionibacteria may be assayed as probiotics for other ruminants like goats and sheep since their milk-derived products are highly appreciated by consumers. It should be emphasized that much of the health benefits described above could be related to the ability of propionibacteria to remain in high numbers in the gastrointestinal tract by surviving the adverse environmental conditions and adhering to the intestinal mucosa. On the basis of the GRAS status of dairy propionibacteria and the positive results obtained by us and other authors, further studies are encouraged in order to select the appropriate strains for developing new functional foods that include these bacteria for human and animal nutrition.